PERFORMANCE OF RAPID ANTIGEN TEST IN COMPARISON TO REAL-TIME RT-PCR IN DIAGNOSIS OF COVID-19 INFECTION: A SHORT STUDY - BISWAS, ARITRA; RAY, RAJA; KHAMRAI, ARPITA; PAUL, DIPANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The global pandemic of Coronavirus Disease 2019 (COVID-19) is still spreading. Because of this, it is urgently necessary to develop quick, easy, and accurate assays to identify severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. For the purpose of diagnosing COVID-19 cases, the quick SARS-CoV-2 antigen detection test’s performance attributes should be assessed and contrasted with the gold standard real-time reverse transcription-polymerase chain reaction (RT-PCR) assay. Methods: A retrospective analysis was done during January to May, 2022 at IPGME&R and SSKM Hospital, Kolkata, India. 2842 paired samples were taken from all patients reporting to the hospital for Rapid Antigen Test (RAT) and RT-PCR. The sensitivity and specificity were calculated to evaluate the performance of the RAT. Results: Of 2842 samples, 229 (8%) were positive, and 2613 (92%) were negative for SARS-CoV-2 RNA by real-time RT-PCR assay. The rapid SARS-CoV-2 antigen detection test’s sensitivity and specificity were 77.29% (177 out of 229) and 99.54% (2601 out of 2613), respectively. Positive predictive value was 93.65% and negative predictive value was 93% with the Ct value ≤35 of real-time RT-PCR result. Conclusion: RAT-positive samples are also positive by real-time RT-PCR test though RAT-negative patient with symptom, should further test for real-time RT-PCR as sensitivity is bit low particularly in symptomatic patient respect to real-time RT-PCR result. Hence, we can conclude that specificity- and sensitivity-wise real-time RT-PCR method is best, but during pandemic/outbreak situation, RAT is good alternative for fast screening and point-of-care test of COVID-19 detection.